Preparation and characterization of temperature‐responsive Ca–alginate/poly(N‐isopropylacrylamide) hydrogel. Issue 2 (17th October 2022) - Tang, Qichen; Qian, Shanhua; Chen, Weiwei; Song, Xiaofei; Huang, Jianfeng
Abstract: Poly( N ‐isopropylacrylamide) (PNIPAm) is widely implemented in responsive soft actuators. However, there are still defects of low brittleness and poor mechanical properties. Moreover, little attention has been paid to diameter shrinkage deformation of tubular PNIPAm hydrogels. In this study, physical crosslinking between Ca 2+ cations and sodium alginate (SA) was introduced to form an interpenetrating network with chemically crosslinked PNIPAm, and then Ca–alginate/PNIPAm hydrogels were prepared. Molecular structure, surface morphology, swelling properties and mechanical properties were characterized. The results indicated that the pure PNIPAm hydrogel obtained using thermal initiation polymerization had better swelling and temperature‐responsive properties (with a maximum swelling ratio of 1134.65% and a fastest decrease rate of 318.45% min −1 in swelling ratio) compared to the hydrogel using ultraviolet polymerization. The mechanical properties the Ca/PNIPAm hydrogel were enhanced until the SA concentration exceeded 8 wt%. The compressive modulus of the hydrogel with SA concentration of 8 wt% (16.61 kPa) was increased by 10 times as compared with the pure PNIPAm hydrogel (1.42 kPa), and its corresponding elastic modulus increased by 47%. Moreover, a model soft actuator was prepared based on annular and tubular hydrogels. It had reversible diameter shrinkage behavior at 50 °C, and excellent temperature‐responsive property. The results reported herein provide valuable insight into the engineering application of temperature‐responsive PNIPAm‐based hydrogels. © 2022 Society of Industrial Chemistry. Abstract : Ca–alginate/poly( N ‐isopropylacrylamide) (PNIPAm) hydrogel with excellent mechanical properties was synthesized by introducing an interpenetrating network with hybrid physically crosslinked alginate and chemically crosslinked PNIPAm for further applications in soft actuators.